2020
DOI: 10.2174/1874434602014010260
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Honey against Methicillin-Resistant and Sensitive Staphylococcus Aureus Isolated from Patients with Diabetic Foot Ulcer

Abstract: Introduction: Staphylococcus aureus is the most important causative agent of wound infections, including diabetic foot ulcers. Honey is a very useful nutrient with antimicrobial properties and other biological properties such as antitumor, anti-inflammatory, antioxidant and antiviral properties. The aim was to examine the antibacterial activity of honey against methicillin-resistant and sensitive S. aureus (MRSA and MSSA) isolated from patients with diabetic foot ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Other studies [49] presented inhibition percentages against S. aureus between 66 and 95% for a 10% honey concentration, so that all the honeys analyzed in this study had greater antimicrobial capacity. In the study by Mirzaei et al [50], lower inhibition percentages were also obtained at higher concentrations of honey (18-40% at a concentration of 25% honey), which corroborates this fact.…”
Section: Antimicrobial Activitysupporting
confidence: 54%
See 1 more Smart Citation
“…Other studies [49] presented inhibition percentages against S. aureus between 66 and 95% for a 10% honey concentration, so that all the honeys analyzed in this study had greater antimicrobial capacity. In the study by Mirzaei et al [50], lower inhibition percentages were also obtained at higher concentrations of honey (18-40% at a concentration of 25% honey), which corroborates this fact.…”
Section: Antimicrobial Activitysupporting
confidence: 54%
“…Other studies [49] presented inhibition percentages against S. aureus between 66 and 95% for a 10% honey concentration, so that all the honeys analyzed in this study had greater antimicrobial capacity. In the study by Mirzaei et al [50], lower inhibition percentages were Other researchers described higher antimicrobial activity in honeydew honeys than in blossom honeys [13,44], relating dark honeys with higher polyphenol compounds and higher biological activities [47]. Heather honeys are dark honeys, and in previous research, they showed higher phenolics contents than honeydew honeys [48], so it is likely that those compounds contribute to antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 91%
“…Honey type is a crucial factor determining the levels of phenolic and flavonoid compounds and, thus, different antibacterial behaviors. In dark forest honey and honeydew honey, these compounds performed successfully against Gram-positive and Gram-negative bacteria [136][137][138][139][140][141].…”
Section: Php?ids[]=saandids[]=egandids[]=ptandids[]=b Randids[]=it (A...mentioning
confidence: 99%